A CRITICAL REVIEW ON SINDUVARA (VITEX NEGUNDO) WITH SPECIAL REFERENCE TO VISHA CHIKITSA - Baghel, *Sachinkumar; Ginode, Atul G.; G V, Karunakar (International Journal of Ayurveda and Pharma Research, 2017)
Sinduvara (Vitex negundo) is a deciduous shrub naturalized in many parts of the world including India. It is used in all systems of treatment â€“ Ayurveda, Unani, Siddha, Homeopathy and Allopathy. Referred to as Sindhuvara and Nirgundi in Ayurveda, it has been used as medicine since ancient times. It is taken in a variety of ways, both internally and externally. The whole plant, leaves, leaf oil, roots, fruits and seeds are administered in the treatment of specific diseases. However, in Ayurveda, the leaves, roots and bark are the most important parts. According to recent researches, the extracts of the plant shows the potential as an antidote for snake poisoning. The plant also exhibits CNS depressant, anti-convulsant, enzyme inhibiting, anti-cancer and anti-bacterial activities. As per Ayurved classics, it is included in the Vishaghna gana (Anti poisonous drugs) and is an important constituent of several Agadas (Anti-poisonous formulations). Agada, one of the modality used for treatment of poisoning is a combination of different herbs. During the study, it was found that Sinduvara is included in nearly 10 Agadas which are mostly used in case of Jangam visha (poisonous bites). So this review paper is an attempt of the author to explore the medicinal value of Sinduvara and highlight the Vishaghna property based on its pharmacological activity.